Redescription of Hemieuryale pustulata von Martens, 1867 (Echinodermata, Ophiuroidea) based on Brazilian specimens, with notes on systematics and habitat association - Gondim, Anne Isabelley; Dias, Thelma Lúcia Pereira; Christoffersen, Martin Lindsey; Stöhr, Sabine (Zootaxa, 2015)
We redescribe Hemieuryale pustulata on the basis of 325 specimens obtained from the continental shelf off northeastern and southeastern Brazil. This is the first record of the species for Brazil. We illustrate for the first time details of the dental plate, oral plate, and vertebrae. Few morphological variations were observed in our extensive material. All specimens were associated with the gorgonian Nicella guadalupensis, suggesting an obligatory association in the Brazilian littoral. H. pustulata did not reveal a particular pattern of distribution on its host gorgonian, but larger gorgonians tend to support a larger number of ophiuroids. In addition to expanding the knowledge on morphology and ecology, we extend the known bathymetric distribution of the species, which is now known from 18 to 330 m.